Problems With The Use Of Waqf Land On The River Banks in Kumai District - Nur Aini; Rofi'i; Haidi Hajar Widagdo; Wahyu Akbar (LP2M IAIN Palopo, 2026)
This study aims to analyze the impact of river abrasion on the use of waqf land in the riverbank area of Kumai District, West Kotawaringin Regency. Waqf land in this region is vulnerable to environmental changes, especially river abrasion, which has the potential to threaten the physical existence and sustainability of social, religious, and educational functions. This research uses a qualitative method with a descriptive approach through case studies. Data collection was carried out through field observations, in-depth interviews with nazhir, mosque administrators, religious leaders, and the surrounding community, as well as documentation. The results of the study showed that river abrasion caused a shrinkage of waqf land from 40 × 40 meters to 35 × 40 meters. The impact can be seen in the damage to part of the mosque foundation, changes in the pattern and direction of building renovation, and the narrowing of the space of the Al-Qur'an Education Park (TPA) which has an impact on rearranging learning times. Nevertheless, the main function of waqf land as a means of worship, education, and social activities can still be maintained through various forms of adaptation carried out by the community and nazhir. This study also found that community participation and the role of nazhir are very decisive in maintaining the sustainability of waqf land utilization, although mitigation efforts are still limited. Therefore, integrated and adaptive waqf land management is needed by involving local governments and religious institutions to protect waqf assets from the threat of abrasion in a sustainable manner.